(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Endometriosis is a common gynaecological disorder which is found in about5% of women and in 30% of infertile women. Identification of risk factors and timely interventionis useful. Methods: A case control study was conducted in the Dept. of obs & gynae of BangabandhuSheikh Mujib Medical University, Shahbag, Dhaka, from October 2015 to March 2016 on50 infertile patients attending the Infertility unit of the institute with the objective to determinethe risk factors of endometriosis. Twenty five women with endometriosis was taken ascases (group-I) and twenty five women without endometriosis was taken as controls(group-II). Result: The mean age was 32.8±5.4 years in group I and 35.1±5.7 years in group II which issimilar. Urban residents were 3.21 times (with 95% CI 0.87-12.71%) more likely to developendometriosis than rural resident which was statistically significant (p<0.05).Among the study population BMI of 72% patients in group I and 68% in group II were within19-24 kg/m2. The difference was not statistically significant (p>0.05) . There was notstatistically significant difference (p>0.05) between two groups in OCP use (84%vs80%).Women with endometriosis had less physical activity than the women without endometriosis;the differences was statistically significant (p<0.05). Consumption of caffeine, red meat,vegetables and fruits has no effect on endometriosis. Women with pain during menstruationwere 29.33 times (with 95% CI 5.17-100%) and women with heavy amount of blood flow were5.09 times (with 95% CI 1.24-22.06%) more likely to be endometriosis, which was statisticallysignificant (p<0.05) . Other risk factors like- age, occupation, educational status, age atmenarche and cycle length were not significantly (p>0.05) associated with endometriosis. Conclusion: Urban residence and all types of physical activities d”1 hour per day weresignificantly higher in infertile women with endometriosis. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(2) : 131-139